(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article outlines ideas about the integrated approaches used in teaching mathematics in higher education institutions. To assist individuals desiring to benefit the worldwide work of Jehovah’s Witnesses through some form of charitable giving, abrochure entitled Charitable Planning to Benefit Kingdom Service Worldwide has been prepared. Examples illustrate the general acceleration of the curved movement using Pifagor’s theory based on the tangensial acceleration link, which represents a change in the number of times in a unit.